2008
DOI: 10.5713/ajas.2008.60730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Ca-salts of Fatty Acids from Soybean Oil and Linseed Oil on c9,t11-CLA Production in Ruminal Fluid and Milk of Holstein Dairy Cows

Abstract: The objective of this study was to investigate the effect of dietary supplementation with calcium salts of soybean oil fatty acids (CaSO) and linseed oil fatty acids (CaLO) on c9,t11-CLA production in ruminal fluid and milk fat from Holstein dairy cows. Rumen fermentation, lactational performances and fatty acid profiles in ruminal fluid and milk fat were also investigated. Twenty multiparous Holstein dairy cows were allotted randomly into two groups consisting of ten cows in each group according to calving da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 32 publications
11
19
0
1
Order By: Relevance
“…at 0 h in SO and FA diets were significantly higher than those in CO diet. The decrease in ammonia-N was similar to that of supplementation of Ca salts of soybean or linseed fatty acid to dairy feed by Sultana et al (2008), suggesting decrease of deamination in the rumen may have occurred. The numbers of Isotricha sp.…”
Section: Results and Discussion Ruminal Fermentationsupporting
confidence: 56%
See 2 more Smart Citations
“…at 0 h in SO and FA diets were significantly higher than those in CO diet. The decrease in ammonia-N was similar to that of supplementation of Ca salts of soybean or linseed fatty acid to dairy feed by Sultana et al (2008), suggesting decrease of deamination in the rumen may have occurred. The numbers of Isotricha sp.…”
Section: Results and Discussion Ruminal Fermentationsupporting
confidence: 56%
“…The effects of treatments on the ruminal protozoa are shown in Table 2. Sultana et al (2008) did not detect a significant change in the protozoal number in cows fed Ca salts of fatty acids originating from soybean oil or linseed oil. at 0 h in SO and FA diets were significantly higher than those in CO diet.…”
Section: Results and Discussion Ruminal Fermentationmentioning
confidence: 54%
See 1 more Smart Citation
“…The highest oleic acid was found in T 3 treatment and lowest in T 1 treatment. This finding corroborate with the findings of Sultana et al, (2008), who reported that feeding of Ca-Salt of Linseed oil significant decreased the proportion of saturated FA C16:0. They also observed that the proportions of long chain fatty acids, namely, C18:0, C18:1, C18:2, VA and CLA increased significantly (p<0.01 and p<0.05)…”
Section: Resultssupporting
confidence: 93%
“…Penambahan minyak kedelai dalam pakan dilaporkan dapat memperbaiki kualitas kimia daging dan susu yaitu meningkatkan conjugated linoleic acid atau CLA (Sultana et al, 2008;Chen et al, 2008;Fatahnia et al, 2008;Choi 2009). CLA berperan sebagai anti kanker, anti diabetis dan anti kegemukan sehingga kandungan yang tinggi pada daging atau susu merupakan diharapkan dapat meningkatkan sifat fungsional dan nilai ekonomis produk ternak.…”
Section: Pendahuluanunclassified